Trajetória do sindicato dos profissionais em educação no ensino municipal (SINPEEM): 1986 - 2004 - Matos, Alessandro Rubens de (2010)
This paper studies the trajectory of the Association of Professionals in Higher Education Hall (SINP), between 1988-2004. We seek to understand the role of this union in a historical-social process and hereby authorized to establish and analyze some of the important aspects of their work with the class teacher in São Paulo. Our goal was to bring to the field of research, in education, studies that are concerned with the experiences and forms of political and trade union of teachers, seeking to understand them also when they express their worldviews and social criticism in this field arduously built. During the study we present the experiences of the teachers' union movement, especially from the end of 1970, where teachers took to the streets, fighting for social and political rights in education. We also aim to demonstrate the relationship of the Association of Professionals in Higher Education Hall - IPNS with municipal governments and verify the extent to which this entity was able to produce political actions that result in social and economic achievements to the class teacher.